2016
DOI: 10.2807/1560-7917.es.2016.21.6.30130
|View full text |Cite
|
Sign up to set email alerts
|

Inverse trends of Campylobacter and Salmonella in Swiss surveillance data, 1988–2013

Abstract: Clinical isolates of Campylobacter spp. and Salmonella spp. are notifiable in Switzerland. In 1995, Campylobacter replaced Salmonella as the most frequently reported food-borne pathogen. We analysed notification data (1988-2013) for these two bacterial, gastrointestinal pathogens of public health importance in Switzerland. Notification rates were calculated using data for the average resident population. Between 1988 and 2013, notified campylobacteriosis cases doubled from 3,127 to 7,499, while Salmonella case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 26 publications
5
45
0
3
Order By: Relevance
“…in the last 20 years. This is confirmed by the trends of campylobacteriosis and salmonellosis case numbers reported to the NNSID [11]. Similar trends in notification rates were observed in the EU [10] e.g.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…in the last 20 years. This is confirmed by the trends of campylobacteriosis and salmonellosis case numbers reported to the NNSID [11]. Similar trends in notification rates were observed in the EU [10] e.g.…”
Section: Discussionsupporting
confidence: 78%
“…[14, 17]. NNSID data also support GPs’ impressions that young adults and middle-aged people are more frequently affected [11]. More prevalent exposure risks among these groups, such as traveling abroad, eating out and preparing food themselves, as stated by GPs, could be responsible for increased case numbers.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Our previous study also indicated high Salmonella counts in feces in summer, with S. Typhimurium phage type 9 as a predominant serovar (18). Human gastrointestinal infections with Salmonella have been positively correlated with warmer temperatures (35,36), as warmer temperatures can enhance the replication of bacteria. In this study, S. Typhimurium was detected in environmental samples and egg shell wash.…”
Section: Discussionmentioning
confidence: 99%